Separators and electrochemical devices and power devices comprising the same

CN224908367UActive Publication Date: 2026-10-27ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202522412449.5
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-11-13
Publication Date
2026-10-27
Estimated Expiration
2035-11-13

AI Technical Summary

Technical Problem

然而,在传统工艺的热压工序(通常温度为50-85℃)中,隔膜胶层的粘性会被激活;此时,金属锂膜中未完全反应的锂屑会在压力作用下嵌入隔膜胶层,不仅导致电芯厚度异常增加,还会造成两重关键问题:一是活性锂被滞留于隔膜中,致使补锂效率下降;二是隔膜孔隙被堵塞,引发电芯界面阻抗增大

Benefits of technology

[0007]相比现有技术,本申请的有益效果包括:本申请通过在隔膜的基膜上设置特定孔隙率的无机纳米颗粒层和特定85℃储能模量的热响应粘结层,并控制这两层的设置顺序,以使它们协同降低隔膜热压后的厚度膨胀率、残留锂量低及界面阻抗增幅,同时提升补锂效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224908367U_ABST
    Figure CN224908367U_ABST
Patent Text Reader

Abstract

The application discloses a diaphragm and an electrochemical device and an electric device comprising the same, and relates to the technical field of electrochemical energy storage. The application sets an inorganic nanoparticle layer with a specific porosity and a thermal response adhesive layer with a specific 85 DEG C storage modulus on a base film of the diaphragm, controls the setting sequence of the two layers, so that they cooperatively reduce the thickness expansion rate of the diaphragm after heat pressing, the residual lithium amount is low, and the interface impedance increase is amplified, and meanwhile, the lithium supplement efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical energy storage technology, and more particularly to diaphragms and electrochemical devices and electrical devices containing them. Background Technology

[0002] Pre-lithiation technology, by pre-preparing a lithium metal film on the surface of the negative electrode, can compensate for lithium loss during the first cycle of the battery cell. However, in the hot-pressing process of traditional processes (typically at temperatures of 50-85°C), the adhesiveness of the separator layer is activated. At this time, unreacted lithium debris in the lithium metal film becomes embedded in the separator adhesive layer under pressure, leading not only to an abnormal increase in cell thickness but also causing two key problems: first, active lithium is retained in the separator, resulting in a decrease in lithium replenishment efficiency; second, the separator pores are blocked, causing an increase in cell interface impedance. Therefore, developing technologies that can solve the above problems is of great significance for improving the practicality of the pre-lithiation process. Utility Model Content

[0003] Based on the deficiencies of the existing technology, the purpose of this application is to provide a diaphragm and an electrochemical device and an electrical device containing the diaphragm, so as to reduce the thickness expansion rate, residual lithium content and interface impedance increase after hot pressing of the diaphragm, and improve the lithium replenishment efficiency.

[0004] To achieve the above objectives, the first aspect of this application provides a diaphragm comprising: The base film has a first surface and a second surface disposed opposite to each other; A thermally responsive adhesive layer is disposed on the first surface of the base film; An inorganic nanoparticle layer is disposed on the side of the thermally responsive adhesive layer opposite to the base film; The thermally responsive adhesive layer has an energy storage modulus of 20~100MPa at 85℃. The porosity of the inorganic nanoparticle layer is below 10%.

[0005] A second aspect of this application provides an electrochemical device including the aforementioned diaphragm.

[0006] A third aspect of this application also proposes an electrical device that includes the aforementioned electrochemical device.

[0007] Compared with the prior art, the beneficial effects of this application include: by setting an inorganic nanoparticle layer with a specific porosity and a thermally responsive adhesive layer with a specific energy storage modulus at 85°C on the base film of the separator, and controlling the setting order of these two layers, the present application can synergistically reduce the thickness expansion rate, residual lithium content and interface impedance increase after hot pressing of the separator, while improving the lithium replenishment efficiency. Attached Figure Description

[0008] Figure 1This is a schematic diagram of the diaphragm structure in Embodiment 1 of this application, wherein 1-base membrane, 11-first surface of the base membrane, 12-second surface of the base membrane, 2-thermal responsive adhesive layer, and 3-inorganic nanoparticle layer. Detailed Implementation

[0009] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. The embodiments of this application may omit unnecessary detailed descriptions. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art.

[0010] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0011] Additionally, quantities, ratios, and other values ​​are sometimes presented in range format in this document. It should be understood that such range format is for convenience and brevity and should be interpreted flexibly to include not only values ​​explicitly defined as range limits, but also all individual values ​​or subranges covered within the range, as if each value and subrange were explicitly defined.

[0012] According to a first aspect of this application, a diaphragm is provided comprising: The base film has a first surface and a second surface disposed opposite to each other; A thermally responsive adhesive layer is disposed on the first surface of the base film; An inorganic nanoparticle layer is disposed on the side of the thermally responsive adhesive layer opposite to the base film; The thermally responsive adhesive layer has an energy storage modulus of 20~100MPa at 85℃. The porosity of the inorganic nanoparticle layer is below 10%.

[0013] The separator has an inorganic nanoparticle layer and a thermally responsive adhesive layer arranged in a specific order on its base film. The inorganic nanoparticle layer has a porosity of less than 10% and a dense structure, which can prevent the physical embedding of lithium debris from the lithium metal film of the negative electrode. The thermally responsive adhesive layer has a high storage modulus at 85°C and maintains high surface hardness during hot pressing, further preventing lithium debris embedding. Through the synergistic effect of the inorganic nanoparticle layer and the thermally responsive adhesive layer, not only are the increases in thickness expansion, residual lithium content, and interfacial impedance after hot pressing of the separator low, but the lithium replenishment efficiency is also high. "Thermoresponsive adhesive" refers to the adhesiveness that develops under heating conditions.

[0014] For example, the porosity of the inorganic nanoparticle layer is within the range of any one or both of 10%, 9.5%, 9%, 8.5%, 8%, 7.5%, 7%, 6.5%, 6%, 5.5%, 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, and 1%. In some embodiments, the porosity of the inorganic nanoparticle layer is 5% to 10% to make the layer structure more compact, which can better prevent the physical embedding of lithium debris, reduce the thickness expansion rate, residual lithium content, and interfacial resistance after hot pressing of the separator, and improve lithium replenishment efficiency.

[0015] The porosity of the inorganic nanoparticle layer was determined using mercury intrusion porosimetry (MIP). The dried membrane sample was placed in a dilatometer, and mercury was immersed into the sample under vacuum, followed by a gradual increase in pressure. The porosity of the coating was calculated based on the relationship between the volume of mercury entering the pores and the applied pressure.

[0016] For example, the energy storage modulus at 85°C of the thermally responsive adhesive layer is a range formed by any one or both of the following: 20 MPa, 30 MPa, 40 MPa, 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa, and 100 MPa.

[0017] The storage modulus at 85℃ of the thermally responsive adhesive layer was determined using dynamic thermomechanical analysis (DMA). The testing instrument was a dynamic thermomechanical analyzer with a single cantilever fixture. Independent thin films made from the corresponding functional layer material were cut into rectangular samples 20 mm long and 5 mm wide. Under a nitrogen atmosphere, the samples were scanned from -50℃ to 150℃ at a frequency of 1 Hz, a strain amplitude of 1 μm, and a heating rate of 5℃ / min to obtain the storage modulus-temperature curve. The storage modulus value at 85℃ was then directly read.

[0018] In some embodiments, the material of the thermally responsive adhesive layer is a styrene copolymer, a polymethyl methacrylate (PMMA)-based polymer, or an acrylate polymer, such as a polymethyl methacrylate-polybutyl acrylate-polymethyl methacrylate triblock copolymer (PMMA-PnBA-PMMA), a ceramic-polymethyl methacrylate composite material (UCCS-PMMA), or a graphene-polymethyl methacrylate composite material (GPL-PMMA).

[0019] In some embodiments, the particle size D50 of the inorganic nanoparticles in the inorganic nanoparticle layer is 50-200 nm. Controlling the particle size of the inorganic nanoparticles within this range is beneficial for forming a dense structure with low porosity, while ensuring the uniformity of the coating, suitable mechanical strength, and avoiding significant negative impacts on the ionic conductivity of the base film. For example, the particle size D50 of the inorganic nanoparticles in the inorganic nanoparticle layer is any one or a combination of 50 nm, 70 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, and 200 nm.

[0020] In some embodiments, the inorganic nanoparticles in the inorganic nanoparticle layer are selected from silicon dioxide, alumina, or silicon nitride. Silica, alumina, and silicon nitride are highly rigid and can effectively prevent the physical embedding of lithium debris, reducing the membrane thickness expansion rate, residual lithium content, and interface impedance, thereby improving lithium replenishment efficiency.

[0021] In some embodiments, the thickness of the inorganic nanoparticle layer is 0.1~0.3 μm. Controlling the thickness of the inorganic nanoparticle layer within this range allows for minimizing the absolute thickness of the coating while ensuring the formation of an effective physical barrier. This reduces the transport path of lithium ions within the coating, lowers the battery's internal resistance, and maintains the battery's energy density. For example, the thickness of the inorganic nanoparticle layer may be any or a combination of 0.1 μm, 0.12 μm, 0.14 μm, 0.16 μm, 0.18 μm, 0.2 μm, 0.22 μm, 0.24 μm, 0.26 μm, 0.28 μm, and 0.3 μm.

[0022] In some embodiments, the inorganic nanoparticle layer contains 95% to 98% by mass, such as any one or both of 95%, 96%, 97%, and 98%.

[0023] In some embodiments, the inorganic nanoparticle layer further includes a dispersant and a binder, wherein the dispersant comprises 0.5% to 1.5% by mass in the inorganic nanoparticle layer (e.g., any one or both of 0.5%, 0.7%, 1%, 1.2%, and 1.5%); and the binder comprises 1.5% to 3.5% by mass in the inorganic nanoparticle layer (e.g., any one or both of 1.5%, 2%, 2.5%, 3%, and 3.5%).

[0024] For example, the dispersant includes polyvinylpyrrolidone (PVP), citric acid, or sodium dodecylbenzenesulfonate (SDBS); the binder includes polyacrylic acid (PAA), polyamide (PAA-HCl), or vinylidene fluoride (PVDF).

[0025] In some embodiments, the thickness ratio of the thermally responsive adhesive layer to the inorganic nanoparticle layer is 1.0 to 2.5:1, preferably 1.2 to 2.0:1. Controlling the thickness ratio within this range can achieve the following synergistic benefits: Ensuring adhesion and desorption functions: When the ratio of the thickness of the thermally responsive adhesive layer to the thickness of the inorganic nanoparticle layer is greater than 1, it can ensure that the thermally responsive adhesive layer has sufficient adhesion at room temperature to achieve tight bonding between the separator and the electrode, and generate stronger thermally induced desorption force during hot pressing, which is beneficial to severing the adhesive connection with lithium scrap.

[0026] Maintaining barrier function and low internal resistance: When the ratio of the thickness of the thermally responsive adhesive layer to the thickness of the inorganic nanoparticle layer is less than 2.5, it can not only ensure that the inorganic nanoparticle layer forms a continuous, dense physical barrier with sufficient mechanical strength to prevent lithium debris from embedding, but also weaken the resistance of the thermally responsive adhesive layer to lithium ion migration and reduce the battery's internal resistance.

[0027] Optimize structural synergy: Controlling the thickness ratio within the range of 1.0 ~ 2.5 : 1, especially within the range of 1.2 ~ 2.0 : 1, optimizes the spatial ratio of these two layers (equivalent to the "intelligent desorption layer" and the "rigid barrier layer"), which helps to achieve a better balance and synergy between their functions and jointly solve the problem of lithium debris embedding and adhesion.

[0028] In some embodiments, the thickness of the thermally responsive adhesive layer is 0.2~0.5 μm. Controlling the thickness of the thermally responsive adhesive layer within this range ensures both strong adhesion and thermal responsiveness, while reducing the path and resistance of lithium ions through the layer, decreasing internal resistance, and improving rate performance. For example, the thickness of the thermally responsive adhesive layer is any or a combination of 0.2 μm, 0.22 μm, 0.24 μm, 0.26 μm, 0.28 μm, 0.3 μm, 0.32 μm, 0.34 μm, 0.36 μm, 0.38 μm, 0.4 μm, 0.42 μm, 0.44 μm, 0.46 μm, 0.48 μm, and 0.5 μm.

[0029] In some embodiments, the total thickness of the inorganic nanoparticle layer and the thermally responsive adhesive layer is 0.3~0.8 μm. Controlling the total thickness of the inorganic nanoparticle layer and the thermally responsive adhesive layer within this range not only prevents the physical embedding of lithium debris, reduces the membrane thickness expansion rate, residual lithium content, and interfacial impedance, and improves lithium replenishment efficiency, but also does not degrade the battery's internal resistance and energy density. For example, the total thickness of the inorganic nanoparticle layer and the thermally responsive adhesive layer may be any one or both of 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, and 0.8 μm.

[0030] In some embodiments, the base film material is, but is not limited to, polyolefins, polyacetals, polyamides, polyesters, polyethylene terephthalate, polycarbonate, polyimide, polyetherketones, polyethersulfones, polyphenylene ethers, polyphenylene sulfides, polyacrylonitrile, polyvinylidene fluoride, polyoxymethylene, polyoxymethylene, polysulfone, polymethyl methacrylate, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, or polytetrafluoroethylene. Some non-limiting examples of polyolefins include polyethylene (PE), ultra-high molecular weight polyethylene (UHMWPE), high-density polyethylene (HDPE), polypropylene (PP), polyethylene-polypropylene copolymer (PE-PP), or polyethylene-polypropylene-polyethylene copolymer.

[0031] In some embodiments, the method for preparing the diaphragm includes the following steps: Inorganic nanoparticles, dispersant and binder are added to the first solvent and dispersed to obtain an inorganic nanoparticle layer slurry. The thermally responsive adhesive polymer was dissolved in a second solvent and dispersed to obtain a thermally responsive adhesive slurry with a solid content of [missing information]. A thermally responsive adhesive layer slurry is applied to the first surface of the base film. After drying, the thermally responsive adhesive layer slurry is applied to the side of the formed thermally responsive adhesive layer away from the base film. After drying and calendering, a diaphragm is obtained.

[0032] For example, the first solvent includes N-methylpyrrolidone (NMP), water, or methylacetamide (DMAc).

[0033] For example, the second solvent includes water or ethanol.

[0034] For example, the solid content of the inorganic nanoparticle layer slurry is 40% to 50%.

[0035] For example, the solid content of the thermally responsive adhesive slurry is 15% to 30%.

[0036] According to a second aspect of this application, an electrochemical device is provided, comprising the diaphragm.

[0037] In some embodiments, a negative electrode sheet is also included, wherein at least one side of the negative electrode sheet is provided with a lithium metal film, and a first surface of the base film faces the lithium metal film.

[0038] In some embodiments, a positive electrode sheet is also included. The separator is disposed between the positive electrode sheet and the negative electrode sheet.

[0039] According to a third aspect of this application, an electrical device is proposed, including the electrochemical device. For example, the electrical device may be selected as a 3C product, such as a mobile phone, tablet, computer, watch, etc.

[0040] Example 1 This embodiment provides a diaphragm, the structural schematic of which is shown below. Figure 1 As shown, it includes: The base film 1 has a first surface 11 and a second surface 12 disposed opposite to each other; A thermally responsive adhesive layer 2 is disposed on the first surface 11 of the base film 1; An inorganic nanoparticle layer 3 is disposed on the side of the thermally responsive adhesive layer 2 facing away from the base film 1. The preparation method of the diaphragm in this embodiment is as follows: Preparation of inorganic nanoparticle layer slurry: SiO2 nanoparticles with a particle size of 100nm and SiO2 nanoparticles with a particle size of 30nm were graded at a mass ratio of 96:4 to obtain a graded material. The graded material and dispersant (PVP, mass of 0.8% of the total mass of the graded material) were added to NMP and stirred and dispersed. Then, binder (polyacrylic acid PAA, mass of 2.2% of the total mass of the graded material) was added and stirred and dispersed to obtain an inorganic nanoparticle layer slurry with a solid content of 45%. Preparation of thermally responsive adhesive slurry: Dissolve UCCS-PMMA (Huizhou Liwei Electronics Technology Co., Ltd., YC-SCD-9052E6-6E3) in NMP to prepare a thermally responsive adhesive slurry with a solid content of 25%; Coating and calendering: The thermally responsive adhesive layer slurry was coated onto the first surface of the PE base film. After drying, the thermally responsive adhesive layer slurry was coated again, dried, and calendered to obtain the separator. The porosity of the inorganic nanoparticle layer, the thickness of the inorganic nanoparticle layer and the thermally responsive adhesive layer in this separator are shown in Table 1.

[0041] Example 2 The differences between this embodiment and Embodiment 1 are as follows: Preparation of inorganic nanoparticle layer slurry: Al2O3 nanoparticles with a particle size of 80nm and Al2O3 nanoparticles with a particle size of 20nm were graded at a mass ratio of 97:3 to obtain a graded material. The graded material and a dispersant (citric acid, with a mass of 0.5% of the total mass of the graded material) were added to deionized water and stirred to disperse. A binder (polyamide PAA-HCl, with a mass of 1.5% of the total mass of the graded material) was added and stirred to disperse, resulting in an inorganic nanoparticle layer slurry with a solid content of 48%. Preparation of thermally responsive adhesive slurry: Dissolve GPL-PMMA (Huizhou Liwei Electronics Technology Co., Ltd., YC-SCD-9376X4-103) in NMP to prepare a thermally responsive adhesive slurry with a solid content of 20%; Coating and calendering: The thermally responsive adhesive layer slurry was coated onto the first surface of the PE base film. After drying, the thermally responsive adhesive layer slurry was coated again, dried, and calendered to obtain the separator. The porosity of the inorganic nanoparticle layer, the thickness of the inorganic nanoparticle layer and the thermally responsive adhesive layer in this separator are shown in Table 1.

[0042] Comparative Example 1 The difference from Example 1 is as follows: the solid content of the prepared inorganic nanoparticle layer slurry is 30%. The porosity of the inorganic nanoparticle layer, the thickness of the inorganic nanoparticle layer and the thermally responsive adhesive layer in this membrane are shown in Table 1.

[0043] Comparative Example 2 The difference from Example 2 is as follows: GPL-PMMA of equal mass is completely replaced with PVDF (polyvinylidene fluoride). The porosity of the inorganic nanoparticle layer, the thickness of the inorganic nanoparticle layer, and the thermally responsive adhesive layer in this membrane are shown in Table 1.

[0044] Comparative Example 3 The difference from Example 1 is as follows: no inorganic nanoparticle layer slurry was prepared and used, and UCCS-PMMA was completely replaced with PVDF (same as Comparative Example 2). The thickness of the thermally responsive adhesive layer is shown in Table 1.

[0045] The separators of the above embodiments and comparative examples are assembled into batteries as follows: Preparation of negative electrode sheet: Graphite, conductive agent acetylene black, binder styrene-butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC) are mixed in deionized water at a mass ratio of 96:1:2:1 to form a slurry, which is coated on copper foil current collector. After drying, cold pressing and slitting, a pre-lithiated negative electrode sheet is obtained on the negative electrode surface by calendering and lithium supplementation. Preparation of the positive electrode sheet: Lithium cobalt oxide (positive electrode active material), acetylene black (conductive agent), and polyvinylidene fluoride (PVDF) (binder) were mixed in an N-methylpyrrolidone solvent at a mass ratio of 95:3:2 to form a slurry. This slurry was coated onto an Al foil (positive electrode current collector), dried, cold-pressed, and slit to obtain the positive electrode sheet. The compacted density of the positive electrode sheet was 4.20 g / cm³. 3 ; Preparation of electrolyte: A solution prepared by mixing lithium salt LiPF6 with a non-aqueous organic solvent (component ratio: ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): ethylene carbonate (VC)) = 20:30:20:28:2, by mass ratio) at a mass ratio of 8:92 is used as the electrolyte for lithium-ion secondary batteries. The negative electrode, positive electrode, and separator are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation, and the first surface of the base film facing the lithium metal film of the negative electrode. The resulting battery is then wound to obtain a bare cell. The bare cell is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and capacity testing (including simultaneous hot pressing during formation and capacity testing), the battery is obtained. The formation procedure is as follows: at 80℃, stand for 1 min, then increase the voltage from 0.1°C to 4.5V / 4.53V; stand for 1 min, then increase the voltage from 0.5°C to 4.5V / 4.53V; stand for 1 min, then increase the voltage from 1.2°C to 4.5V / 4.53V. The capacity testing procedure is as follows: at 80℃, discharge at 0.5C CC to 4.5V, CV to 0.02C, let stand for 5 minutes, discharge at 0.2C constant current to 3.0V, let stand for 5 minutes, discharge at 0.5C CC to 4.0V, CV to 0.02C.

[0046] The following performance tests were performed on these batteries: Diaphragm thickness expansion rate after hot pressing: Measure the diaphragm thickness before and after hot pressing with a micrometer and calculate the thickness expansion rate.

[0047] Lithium content in the separator: After formation, the separator is removed from the battery and cleaned and dissolved with DMC (dimethyl carbonate). The total amount of lithium in the solution is measured by inductively coupled plasma atomic emission spectrometry.

[0048] Membrane interfacial impedance increase: The interfacial impedance (Rsei) of the battery formation was measured by electrochemical impedance spectroscopy (EIS), and its increase relative to the initial impedance was calculated.

[0049] Lithium replenishment efficiency: Calculated from the initial charge-discharge (i.e., formation capacity) capacity, lithium replenishment efficiency = (initial discharge capacity / initial charge capacity) × 100%.

[0050] Storage modulus: The storage modulus of the thermally responsive adhesive layer was determined using dynamic thermomechanical analysis (DMA). The testing instrument was a dynamic thermomechanical analyzer using a single cantilever fixture. Independent thin films of the corresponding functional layer material to be tested were cut into rectangular samples with a length of 20 mm and a width of 5 mm. Under a nitrogen atmosphere, the temperature was scanned from -50 °C to 150 °C at a frequency of 1 Hz, a strain amplitude of 1 μm, and a heating rate of 5 °C / min to obtain the storage modulus-temperature curve. The storage modulus value at 85 °C was then directly read.

[0051] The test results are shown in Table 1.

[0052] Table 1 As can be seen from the above test data, the membrane of this application has low thickness expansion rate, residual lithium content and interface resistance after hot pressing, and high lithium replenishment efficiency. For example, the membrane thickness expansion rate after hot pressing is less than 5%, the residual lithium content is less than 0.4 mg / Ah, the interface resistance increase is less than 9%, and the lithium replenishment efficiency is more than 93%.

[0053] In Comparative Example 1, the high porosity of the inorganic nanoparticle layer caused lithium debris in the lithium metal film of the negative electrode to easily embed itself during hot pressing, resulting in a higher increase in the membrane thickness expansion rate, residual lithium content, and interface impedance after hot pressing, and a lower lithium replenishment efficiency.

[0054] In Comparative Example 2, the thermal response adhesive layer has a low surface hardness at 85°C, which makes it easy for lithium debris to be physically embedded in it during hot pressing. This results in a higher increase in the membrane thickness expansion rate, residual lithium content, and interface impedance after hot pressing, and a lower lithium replenishment efficiency.

[0055] Comparative Example 3 uses a common separator. During the hot pressing process, lithium debris from the lithium metal film of the negative electrode is easily embedded in it, resulting in a higher increase in the separator thickness expansion rate, residual lithium amount and interface impedance after hot pressing, and a lower lithium replenishment efficiency.

[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A diaphragm, characterized in that, include: The base film has a first surface and a second surface disposed opposite to each other; A thermally responsive adhesive layer is disposed on the first surface of the base film; An inorganic nanoparticle layer is disposed on the side of the thermally responsive adhesive layer opposite to the base film; The thermally responsive adhesive layer has an energy storage modulus of 20~100MPa at 85℃. The porosity of the inorganic nanoparticle layer is below 10%.

2. The diaphragm as described in claim 1, characterized in that, The porosity of the inorganic nanoparticle layer is 5%~10%.

3. The diaphragm as described in claim 1, characterized in that, The material of the thermally responsive adhesive layer is a styrene copolymer, a polymethyl methacrylate polymer, or an acrylate polymer.

4. The diaphragm as described in claim 1, characterized in that, The inorganic nanoparticles in the inorganic nanoparticle layer have a particle size D50 of 50~200 nm.

5. The diaphragm as described in claim 1, characterized in that, The inorganic nanoparticles in the inorganic nanoparticle layer are selected from silicon dioxide, aluminum oxide, or silicon nitride.

6. The diaphragm as described in claim 1, characterized in that, The ratio of the thickness of the thermally responsive adhesive layer to the thickness of the inorganic nanoparticle layer is 1.0 ~ 2.5 :

1.

7. The diaphragm as described in claim 1, characterized in that, The thickness of the inorganic nanoparticle layer is 0.1~0.3μm; And / or, the thickness of the thermally responsive adhesive layer is 0.2~0.5μm; And / or, the total thickness of the inorganic nanoparticle layer and the thermally responsive adhesive layer is 0.3~0.8μm.

8. An electrochemical device, characterized in that, Includes the diaphragm as described in any one of claims 1 to 7.

9. The electrochemical device as described in claim 8, characterized in that, It also includes a negative electrode sheet, on at least one side of which is provided with a lithium metal film, and the first surface of the base film faces the lithium metal film.

10. An electrical appliance, characterized in that, The electrochemical device includes any one of claims 8 to 9.